Inovasi Pembelajaran Sejarah Pemikiran Ekonomi Pada Generasi –Z: Higher Order Thinking Skills (HOTS) Based - Siti Hodijah; Faradina Zevaya; Dwi Hastuti (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2021)
The learning model commonly used in the History of Economic Thought course is a conventional model. This model is considered less in accordance with the characteristics of Generation Z who tend to like modern methods. The research method or evaluation carried out in this study is using student self-assessment. In self-assessment, students evaluate the overall process of learning action or action on concepts through performance outcomes or products. The project-based learning model (PjBL) is based on a constructivist learning theory based on the idea that students acquire knowledge based on their own experience. To complement PjBL innovation, it is accompanied by an ability assessment, namely Higher Order Thinking Skills (HOTS). Where HOTS requires students to build their own knowledge and apply knowledge so as to produce output that can be useful. The results of the study show that the Project Based Learning (PjBL) learning model with Higher Order Thinking Skills (HOTS) innovation has a very positive influence on increasing students' critical thinking power and can trigger students' enthusiasm and activeness in the learning process.